Temporal trend in mortality due to congenital heart disease in China from 2008 to 2021 - Youping Tian; Xiaojing Hu; Qing Gu; Miao Yang; Pin Jia; Xiaojing Ma; Xiaoling Ge; Quming Zhao; Fang Liu; Ming Ye; Weili Yan; Guoying Huang; et al. (Chinese Medical Journal)
Abstract. Background:. Congenital heart disease (CHD) is a leading cause of birth defect-related mortality. However, more recent CHD mortality data for China are lacking. Additionally, limited studies have evaluated sex, rural–urban, and region-specific disparities of CHD mortality in China. Methods:. We designed a population-based study using data from the Dataset of National Mortality Surveillance in China between 2008 and 2021. We calculated age-adjusted CHD mortality using the sixth census data of China in 2010 as the standard population. We assessed the temporal trends in CHD mortality by age, sex, area, and region from 2008 to 2021 using the joinpoint regression model. Results:. From 2008 to 2021, 33,534 deaths were attributed to CHD. The period witnessed a two-fold decrease in the age-adjusted CHD mortality from 1.61 to 0.76 per 100,000 persons (average annual percent change [AAPC] = −5.90%). Females tended to have lower age-adjusted CHD mortality than males, but with a similar decline rate from 2008 to 2021 (females: AAPC = −6.15%; males: AAPC = −5.84%). Similar AAPC values were observed among people living in urban (AAPC = −6.64%) and rural (AAPC = −6.12%) areas. Eastern regions experienced a more pronounced decrease in the age-adjusted CHD mortality (AAPC = −7.86%) than central (AAPC = −5.83%) and western regions (AAPC = −3.71%) between 2008 and 2021. Approximately half of the deaths (46.19%) due to CHD occurred during infancy. The CHD mortality rates in 2021 were lower than those in 2008 for people aged 0–39 years, with the largest decrease observed among children aged 1–4 years (AAPC = −8.26%), followed by infants (AAPC = −7.01%). Conclusions:. CHD mortality in China has dramatically decreased from 2008 to 2021. The slower decrease in CHD mortality in the central and western regions than in the eastern regions suggested that public health policymakers should pay more attention to health resources and health education for central and western regions.